2022
DOI: 10.3390/ph15020255
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Sex-Related Differences in Normal Tissue Effects Induced by Platinum Compounds

Abstract: Gender medicine in the field of oncology is an under-researched area, despite the existing evidence towards gender-dependent response to therapy and treatment-induced adverse effects. Oncological treatment aims to fulfil its main goal of achieving high tumour control by also protecting normal tissue from acute or chronic damage. Chemotherapy is an important component of cancer treatment, with a large number of drugs being currently in clinical use. Cisplatin is one of the most commonly employed chemotherapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Gender differences in cisplatin ototoxicity have been reported [ 12 , 24 ]. Sex hormones, particularly estrogen, are thought to have protective effects against hair cell loss in female patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender differences in cisplatin ototoxicity have been reported [ 12 , 24 ]. Sex hormones, particularly estrogen, are thought to have protective effects against hair cell loss in female patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences in cisplatin ototoxicity have been reported [ 12 , 24 ]. Sex hormones, particularly estrogen, are thought to have protective effects against hair cell loss in female patients [ 24 ]. However, the mechanism by which E2 protects against cisplatin-induced hair cell loss is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing awareness of bias and class imbalance sources in medical data sets. Notably, gender [ 16 , 17 ] and race bias [ 18 , 19 ] with class imbalances are increasingly highlighted in the literature. Both factors have been shown to affect outcomes.…”
Section: Sources Of Bias and Class Imbalance In Large Scale Medical Datamentioning
confidence: 99%
“…Retrospective and prospective studies have previously identified potential prognostic and predictive factors grounded in sex differences. Sex differences have been noted in anti-epileptic management [ 70 ], chemotherapy [ 12 , 71 ], and immunotherapy [ 11 , 17 ] ( Table 3 ). Looking ahead at the potential future results of omic analyses will therefore involve looking back at current and previous trials wherein a biospecimen was/is being collected to examine where future conclusions may originate from ( Table 5 ) and how this bedside data connects to bench data, including tissue culture and animal studies.…”
Section: Omics and Biospecimen Analysismentioning
confidence: 99%
“…In the context of glioma, several papers have explored biological factors and sex-dependent differences between men and women and implications related to histology, sex hormones [ 8 , 9 ], pregnancy, menstruation, menopause, and oral contraceptives. There is, however, an ongoing lack of in-depth understanding of the physiology and metabolism that underpins sex differences in glioma, with data just emerging [ 3 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. These biological differences can result in differences in the clinical outcomes of novel interventions.…”
Section: Introductionmentioning
confidence: 99%